CORPORATE DESIGN. ELEMENTS AND DEVELOPMENT STRATEGIES (Innovation in Woodworking Industry and Engineering design, 2026)
The development of design and manufacturing companies follows different stages. In the conditions of continuous competition, the contemporary world features increasing and developing globalization and internationalization of economic processes in the conditions of information and telecommunication revolution. In the paper, the basic elements of corporate design are considered, as the basis of creating an integral concept of corporate identity. A special attention is given to the choice of strategy for the design of serial and individual pieces of furniture.